VALUE ADDED SERVICES IN TERMINALS FOR DANGEROUS GOODS TRANSPORTED BY RAIL - Babin, Matej (Doprava a spoje, 2012)
Value added services (VAS) caused mainly for the reasons of high standard quality requirements and precision production plan fulfillment in moving space, time and in specified sequence. The requirements fulfilled, the lower are the costs on closing the gaps. Lower entry prizes for final products are resulting from lower costs therefore. This article is focused on VAS in terminals for DG.